New model of Oral Mucositis with 5-Fluorouracil chemo-induced in Wistar rats without the use of anesthesics - Wellington Dorigheto Andrade VIEIRA; Fernando Monteiro AARESTRUP; Beatriz Julião Vieira AARESTRUP; Maria das Graças Afonso Miranda CHAVES; Maria Inês da Cruz CAMPOS (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Introduction: Oral mucositis (OM) is considered the most frequent acute side effect of the antineoplasic treatment, with ulcerative lesions resulting from a painful symptomatology, affecting the oral cavity in response to the Antineoplastic treatment. In order to study these side effects, experiments in animal models are necessary, using antineoplastic drugs for the induction of OM and anesthetics, mainly Ketamine and Xylazine, to perform scarification of the cheeks. Objective: The goal is to report an experimental model of induced OM, without the use of anesthetics for the scarification stage of the animal cheeks. Methods: Fourty five male Wistar rats, 7 weeks old and weighting 220g, were used, divided into 2 groups; with OM induced by 5-Fluorouracil intraperitoneal administration. Two days later, Group I was physically contained, in contrast, Group II were anesthetized with Ketamine and Xylazine, focusing on irritating the cheek mucosa using the tip of a sterile needle, in order to potentialize the development of OM. The animals were euthanized with an anesthetic overdose. Results: Concerning the experiment of 5-Fluorouracil chemo-induced of OM, where the irritation was performed by physical containment, without the use of anesthetics (Ketamine and Xylazine), the animals had a longer survivability and a rapid improvement of the side effects induced by chemotherapy. Conclusion: This new model is promising, considering that the use of anesthetics (Ketamine and Xylazine) showed a high mortality rate. In the absence of anesthesia, all the animals survived until the end of the experiment involving chemotherapy model with 5-Fluorouracil and physical restraint.